Perilaku Investasi Saham Syariah Generasi Milenial Di Era 5.0 - Ardiansyah Ardiansyah; Aksi Hamzah; Otong Karyono (Jurnal Ilmiah Al-Tsarwah, 2024)
ABSTRACTThe aim of this research is to analyze the influence of each variable, namely attitudes, subjective norms, perceived behavioral control, and Islamic financial management behavior on investment behavior, the influence of each variable, namely attitude, subjective norms, and perceived behavioral control on financial management behavior. Islamic, the influence of each variable, namely attitudes, subjective norms, and perceived behavioral control on investment behavior through the mediation of Islamic financial management behavior. This type of research is quantitative research for the methodological aspect and a sharia economic approach for the scientific aspect. Data collection methods use questionnaires and interviews. The population in this study was the millennial generation in South Sulawesi using a sample of 180 respondents. These data were tested using the Structural Equation Modeling (SEM) technique with the help of the SmartPLS Version 4 analysis tool. The research results showed that attitudes, subjective norms and perceived behavioral control each had no effect on investment behavior. Islamic financial management behavior has a positive and significant effect on investment behavior. Attitudes and subjective norms each have a positive and significant effect on Islamic financial management behavior, while perceived behavioral control has no effect. Attitudes and subjective norms each influence investment behavior through the mediation of Islamic financial management behavior, while perceived behavioral control has no effect. This research has the implication that seminars on sharia finance must be carried out more actively and investment galleries and stock communities in each city/district need to be formed so that the opportunity to increase the number of sharia stock investors will be greater. Keywords: Attitude, Subjective Norms, Behavioral Control, Investment Financial Management.